Screening of rice genotypes for leaf blast resistance under field condition - Sharma, Pratiksha; Magar, Prem Bahadur; Baidya, Suraj; Yadaw, Ram Baran (Journal of Agriculture and Natural Resources, 2020)
Blast, caused by Pyriculariagrisea (Sacc.) is the most destructive disease of rice in Nepal. To identify the sources of leaf blast resistance in rice genotypes, a field experiment was conducted under natural epiphytotic condition at National Plant Pathology Research Centre (NPPRC), Khumaltar, Lalitpur, Nepal during summer season in 2018 and 2019.A total of 128 rice genotypes in 2018 and 291during 2019 including resistant check (Sabitri) and susceptible check (Shankharika/Mansuli) were tested. Field experiment was conducted in single rod row design. Leaf blast disease assessment was done according to 0-9 scale. During 2018, 59 entries were highly resistant (Score 0), 34 resistant (Score 1), 26 moderately resistant (Score 2-3), 5 were moderately susceptible (Score 4-5), 4 susceptible (Score 6-7) and none of them were highly susceptible (Score 8-9) to leaf blast. Similarly, in 2019, 6 lines were highly resistant, 70 resistant, 196 moderately resistant, 15 lines were moderately susceptible, 4 susceptible and none of them were highly susceptible to the disease. Only, one genotype NR2179-82-2-4-1-1-1-1 (Score 1) was found resistant in both years. Similarly, genotype NR2182-22-1-3-1-1-1 (Score 2-3) was found moderately resistant. Some of the genotypes were found resistant in 2018 which become moderately resistant in 2019, they were NR2180-20-2-5-1-1-1-1, IR97135-8-3-1-3, IR98786-13-1-2-1, NR2181-139-1-3-1-1-1-1, and IR13F402. So, findings of these resistant and moderately resistant genotypes could be used in resistant source for the development of leaf blast resistant rice varieties through hybridization in future.